Reflections on the use of subsidies received from the Agriculture and Rural Development Operational Programme and the European Agricultural Fund for Rural Development in the micro-region Ibrány-Nagyhalász - Nagy, Csilla (Acta Agraria Debreceniensis, 2012)
Hungary’s accession to the European Union caused major changes in the country’s life. Rural development subsidies can be received through extensive application mechanisms. This is particularly challenging for lagging micro-regions. My study presents the lagging microregion of Ibrány-Nagyhalász, focusing on what types of organizations and upon what grounds received subsidies in the framework of the Agriculture and Rural Development Operational Programme 2004–2006 (AVOP). I focus on the same parameters when examining the measures in the third axis of the New Hungary Rural Development Programme 2007–2013 (ÚMVP), followed by a comparison between the two programmes’ effectiveness. I conclude that due to the experience collected throughout the period of AVOP, both the number and the quality of applications have risen from the year 2007. Still, due to the lack of competence, cooperation and motivation, the region’s planned improvements are not yet fully met and the capabilities of the region are not yet fully exploited. For the future, even more complex and more feasible projects are needed.